Neoestetica: un archetipo disciplinare - Luigi Russo (Rivista di Estetica, 2011)
The paper focuses on Du Bos’ contribution to the birth of aesthetics. Du Bos elaborates – in an anticlassicistical tone – three central notions: 1) that of “artificial passion”, 2) of the taste of “the public” (which is in turn linked to a peculiar conception of “feeling”) and 3) of “artistic genius”. The main tenet will be that such an approach does lead to a “philosophy of fine arts” (or of “artistic beauty”), i.e. the discipline with which modern aesthetics ends up identifying at the end of the xviii century. Hence the theoretical, and not just historical, interest for this author, especially when having an eye to neoaesthetics, viz. aesthetics as begotten by the crisis of the modern aesthetics around the middle of the xix century.